Synthesis and sar study of diarylpentanoid analogues as new anti-inflammatory agents - Leong, Sze Wei; Mohd Faudzi, Siti Munirah; Abas, Faridah; Mohd Aluwi, Mohd Fadhlizil Fasihi; Rullah, Kamal; Lam, Kok Wai; Abdul Bahari, Mohd Nazri; Ahmad, Syahida; Chau, Ling Tham; Shaari, Khozirah; Lajis, Nordin H. (MDPI, 2014)
A series of ninety-seven diarylpentanoid derivatives were synthesized and evaluated for their anti-inflammatory activity through NO suppression assay using interferone gamma (IFN-γ)/lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Twelve compounds (9, 25, 28, 43, 63, 64, 81, 83, 84, 86, 88 and 97) exhibited greater or similar NO inhibitory activity in comparison with curcumin (14.7 ± 0.2 µM), notably compounds 88 and 97, which demonstrated the most significant NO suppression activity with IC50 values of 4.9 ± 0.3 µM and 9.6 ± 0.5 µM, respectively. A structure–activity relationship (SAR) study revealed that the presence of a hydroxyl group in both aromatic rings is critical for bioactivity of these molecules. With the exception of the polyphenolic derivatives, low electron density in ring-A and high electron density in ring-B are important for enhancing NO inhibition. Meanwhile, pharmacophore mapping showed that hydroxyl substituents at both meta- and para-positions of ring-B could be the marker for highly active diarylpentanoid derivatives